2017
DOI: 10.3390/s17122842
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Focus Inspection System Using a Position-Sensitive Detector

Abstract: Precise and rapid focus detection is an essential operation in several manufacturing processes employing high-intensity lasers. However, the detection resolution of existing methods is notably low. This paper proposes a technique that provides a rapid-response, high-precision, and high-resolution focus inspection system on the basis of geometrical optics and advanced optical instruments. An ultrafast interface position detector and a single-slit mask are used in the system to precisely signal the focus positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another approach is adding an extra light source as the detective light and introducing an autofocusing system that have been realized based on confocal scheme, [81,82] contrast measurement on a pattern illumination, [83] or PSF engineering including astigmatism method, [84][85][86] bisected beam method, [87] and double-spot focus detection. [88] In the PSF engineering-based techniques, the PSF of the detective laser beam is modulated to have different shapes or positions in different focusing positions.…”
Section: Interface Positioning Methodsmentioning
confidence: 99%
“…Another approach is adding an extra light source as the detective light and introducing an autofocusing system that have been realized based on confocal scheme, [81,82] contrast measurement on a pattern illumination, [83] or PSF engineering including astigmatism method, [84][85][86] bisected beam method, [87] and double-spot focus detection. [88] In the PSF engineering-based techniques, the PSF of the detective laser beam is modulated to have different shapes or positions in different focusing positions.…”
Section: Interface Positioning Methodsmentioning
confidence: 99%
“…Available as two-dimensional sensors with sizes up to 20 mm × 20 mm, they are capable of measuring the laser spot’s weighted center of intensity with micrometer uncertainties. These sensors have been used in the past for similar applications such as fast autofocus inspections [ 9 ] as well as angle measurements of the relative story displacement [ 10 ]. The dynamic potential of the PSD has also been observed in the past [ 11 ], which showed that dynamic measurements with speeds up to 104.72 m/s (=ca.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of mirror-inclination angles or MEMS steering angles with PSDs have been performed by [ 8 , 12 , 13 , 14 ]. Nishibori and Nishibori [ 9 ] focused on a static measurement in a range of ±8° with a measurement uncertainty of 0.5°. Fujita et al [ 8 ] designed a controlling system with an rms error of 0.21° in an angular range between ±6° for a two-dimensional MEMS mirror and a holed PSD, which showed that the dynamic characterization of MEMS with PSDs is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Position-sensitive detector (PSD), a kind of optical inspection systems for the precise measurement of position, distance, displacement, angle, and other relevant physical variables, is a crucial component for diverse applications, including optical engineering, aerospace, real-time tracking and nanorobotics [1][2][3][4]. In tracking or remote measurement systems, high sensitivity and ultra-weak light detection capability are crucial, which determine the accuracy and operating distance of the systems.…”
Section: Introductionmentioning
confidence: 99%